2016
DOI: 10.1590/1980-5497201600020006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida relacionada à saúde em idosos residentes em região de alta vulnerabilidade para saúde de Belo Horizonte, Minas Gerais

Abstract: In addition to the aspects related to social adversity, lifestyle, and health conditions, some functional aspects of social relations were important for understanding the HRQOL in elderly persons living in social vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
0
20
0
17
Order By: Relevance
“…The correlation analysis showed that the higher the number of diseases, the lower the QoL score; and, the higher the intensity of pain, the lower the QoL scores. Regarding CD, the study of Camelo, Giatti and Barreto 19 with 366 old subjects identified that the bigger the number of reported medical diagnostics, the worse is the result of the health-related QoL. The study by Lacerda et al 20 that evaluated 23 old subjects with mean age of 84.22±7.89 years showed that the QoL of the elderly who reported pain was downgraded in relation to those who did not have pain.…”
Section: Discussionmentioning
confidence: 98%
“…The correlation analysis showed that the higher the number of diseases, the lower the QoL score; and, the higher the intensity of pain, the lower the QoL scores. Regarding CD, the study of Camelo, Giatti and Barreto 19 with 366 old subjects identified that the bigger the number of reported medical diagnostics, the worse is the result of the health-related QoL. The study by Lacerda et al 20 that evaluated 23 old subjects with mean age of 84.22±7.89 years showed that the QoL of the elderly who reported pain was downgraded in relation to those who did not have pain.…”
Section: Discussionmentioning
confidence: 98%
“…The score of each domain can vary from 0 to 100, with scores close to 0 representing a worse perception of quality of life while those close to 100, a better perception of quality of life 2.4 . Instruments similar to the SF-36 are also used as quicker to apply alternatives, such as the Medical Outcomes Study 12-Item Short-Form Health Survey (SF-12) 23 and Medical Outcomes Study Short Form 8-Item Health Survey (SF-8) 15 .…”
Section: Quality Of Life Of the Elderlymentioning
confidence: 99%
“…According to the findings of this review, in addition to lifestyle, the factors that influence the quality of life of the elderly are: gender 9,14,15,23 , age 13,15,21,23, schooling 4,13,15,23 , ethnic group 4,23 , physical capacity 4,10,15,21-24 , diseases 4,9,21,23,24 and income 23 . In the study by Camelo et al 23 , women over 70 years of age and with less than four years of schooling had a worse health-related quality of life in the physical and mental domains of SF-12 than men. In the physical domain of this same instrument, black women with incomes less than four times the minimum salary also had a worse quality of life.…”
Section: Quality Of Life Of the Elderlymentioning
confidence: 99%
“…2 Only functional aspects of social relationships, such as dissatisfaction with personal relationships and not having, where necessary, someone's support to help get in bed, going to the doctor and preparing meals were independently associated with poorer quality of life. 3 In the analysis of quality of life in General Quality of Life (GQoL), which is represented by questions one (Q1) and two (Q2) of the WHOQOL -bref questionnaire, it was observed that the elderly, when questioned about their (61.64%), and when asked about their satisfaction with their health, the majority of the elderly (41.9%) showed neither satisfaction nor dissatisfaction , while 30.14% said they were dissatisfied with their health. Regarding the QOL score, the average of the answers to question one (Q1), which evaluates the quality of life in general, and question 2 (Q2), about satisfaction with one's own health was, respectively, 3.0 and 2.78, values closer to three, which corresponds to the intermediate option neither bad, nor good nor neither satisfied nor dissatisfied.…”
Section: Regardingmentioning
confidence: 99%